2018
DOI: 10.1038/s41598-018-31537-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation of potassium channel KCa3.1 and immune signalling pathways is associated with infant immune responses following BCG vaccination

Abstract: Bacillus Calmette–Guérin (BCG) is the only licensed vaccine for tuberculosis (TB) and induces highly variable protection against pulmonary disease in different countries. We hypothesised that DNA methylation is one of the molecular mechanisms driving variability in BCG-induced immune responses. DNA methylation in peripheral blood mononuclear cells (PBMC) from BCG vaccinated infants was measured and comparisons made between low and high BCG-specific cytokine responders. We found 318 genes and 67 pathways with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 61 publications
(66 reference statements)
3
22
0
Order By: Relevance
“…The changes were reflected in the DNA methylome, with the strongest response being recorded within weeks after vaccination 9 . Our observation that BCG induces alterations of the DNA methylome of immune cells has later been confirmed by others 10,11 . Since BCG vaccination reflects an in vivo interaction between immune cells and viable mycobacteria, we hypothesized that natural exposure to M. tuberculosis would induce similar changes not only in TB patients, but also in individuals who have been exposed to TB.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The changes were reflected in the DNA methylome, with the strongest response being recorded within weeks after vaccination 9 . Our observation that BCG induces alterations of the DNA methylome of immune cells has later been confirmed by others 10,11 . Since BCG vaccination reflects an in vivo interaction between immune cells and viable mycobacteria, we hypothesized that natural exposure to M. tuberculosis would induce similar changes not only in TB patients, but also in individuals who have been exposed to TB.…”
Section: Introductionsupporting
confidence: 85%
“…The copyright holder for this this version posted March 20, 2021. ; https://doi.org/10.1101/2021.03.16.21253732 doi: medRxiv preprint this study (dark green) and Hasso-Agopsowicz et al (human BCG vaccine study, light green) 10 , b) Sunburst Plot describing the overlap of enriched GO biological processes emerging from a comparison between the GO data derived from the 185 common DMGs (Figure 4a) and All rights reserved. No reuse allowed without permission.…”
Section: Venn and Overlap Analysesmentioning
confidence: 96%
“…Another important potential application of attenuated strains is for immunological assays. Although BCG has been widely used for this (Hasso-Agopsowicz et al, 2018; Whittaker et al, 2018), it lacks the RD1 region and as a result it does not secrete many immunogenic proteins. Often cytokine production levels are a major concern with regards to host cells infected by attenuated strains, since many of them have essential immunogenic proteins missing.…”
Section: Discussionmentioning
confidence: 99%
“…A secreted Mtb protein, Rv2966c, has been demonstrated to be a 5-methylcytosine-specific DNA methyltransferase, interacting with host chromatin predominantly through non-CpG methylation and histone H3/H4 binding [11]. Two recent studies have shown that protective activity against mycobacterium correlates with altered DNA methylation pattern in immune cells from Bacillus Calmette-Guérin-vaccinated adults and infants, leading to the hypothesis that modulation of epigenetic programming of the cell to induce trained innate immunity may boost early clearance of Mtb upon infection [12][13][14].…”
Section: Introductionmentioning
confidence: 99%